English Under-five Mortality in Thailand based on Confidence Intervals from Log Linear Model: Under-five Mortality in Thailand - Kulharb , Nittaya; Ma-a-lee, Arinda; Tongkumchum, Phattrawan (Al-HIKMAH Journal, 2021)
Under-five mortality rate is one of indicators to understand the position of the country in relation to other countries in terms of public health. Under-five mortality in Thailand is still high. This study aims to investigate trends and geographical variations of under-five mortality in Thailand 2000 to 2009. The data were all reported Thai deaths of under-five years from 2000 to 2009 obtained from Ministry of Public Health. A log linear model based on sum contrasts was fitted to under-five mortality rates as an additive linear function of gender, public health areas (PHA) and year. The model gives adjusted confidence intervals for mortality rates for levels of each determinant adjusted for other factors. Over the decade 2000-2009, there were 84,227 under-five deaths recorded. The log linear model provided a good fit as indicated by residual plot. On average an annual death rate was 177.9 per 100,000 population. Mortality trends tend to decrease with the exception in 2001. High rates occurred in central area (PHA 2, PHA3 and PHA 4) and lower south (PHA12) of Thailand. This study highlighted the locations to which public health authorities should direct their intervention plan.